2019
DOI: 10.1164/rccm.201807-1212ci
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Pneumothorax

Abstract: A genetic influence on spontaneous pneumothoraces-those occurring without a traumatic or iatrogenic cause-is supported by several lines of evidence: 1) pneumothorax can cluster in families (i.e., familial spontaneous pneumothorax), 2) mutations in the FLCN gene have been found in both familial and sporadic cases, and 3) pneumothorax is a known complication of several genetic syndromes. Herein, we review known genetic contributions to both sporadic and familial pneumothorax. We summarize the pneumothorax-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 156 publications
(136 reference statements)
1
38
0
4
Order By: Relevance
“…Indeed, 2 studies showed a prevalence of BHD of 64–86% in patients presenting with apparent PSP and a positive family history of pneumothorax ( 5 , 6 ). It is therefore recommended to systematically look for lung abnormalities and a genetic cause, especially BHD, in any individual presenting with apparent PSP, and even more in case of a positive family history of pneumothorax ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 2 studies showed a prevalence of BHD of 64–86% in patients presenting with apparent PSP and a positive family history of pneumothorax ( 5 , 6 ). It is therefore recommended to systematically look for lung abnormalities and a genetic cause, especially BHD, in any individual presenting with apparent PSP, and even more in case of a positive family history of pneumothorax ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient underwent conservative therapy in the first attack for seven days per pediatric guidelines, even so, this is still debatable and surgeons still in a split decision [ [6] , [7] , [8] , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision for open thoracotomy or VATS is still controversial. The ACCP guidelines recommend a thoracoscopic approach both for PSP and SSP [ 6 ], but a study by Barker et al in 2003 showed fewer recurrence in open (1%) in comparison to VATS [ 14 ]. In 2018 total of 1040 patients underwent a study for the decision of early VATS rather than chest tube management, early VATS is associated with a decreased hospital stay, charges, and readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations